PENGARUH AKTIVITAS PENUNJANG WISATA TERHADAP PERUBAHAN TATA RUANG DESA DAN TATA RUANG RUMAH TINGGAL STUDI KASUS: DESA WISATA BEJIHARJO, YOGYAKARTA (The Influence of Tourism Supporting Activity toward The Spatial Changes in Village and houses, Case Study - Fajari, Safinta Rhosa; Suprapti, Atiek; Supriyadi, Bambang (Tesa Arsitektur, 2014)
Yogyakarta is the Indonesiaâs province that has strong traditional tourism attractions. One of them is tourism villages. This study was taken place in Desa Wisata Bejiharjo, Kecamatan Karangmojo, Kabupaten Gunungkidul, Yogyakarta. The purpose of this study was to know the spatial change that has occured in Dusun Glaran I and Dusun Bulu as a result of the addition of new activities as tourism villages, and further to know the factors that has affected to the changes. This study used the qualitative rationalistic method with spatial and socio-cultural theory as the grand theory based on related theory. Data collection was done by observation and purposive sampling interview. Data analysis was done based on the variables formulated. In conclusion, the spatial space in Desa Bejiharjo has changed. The spatial space in Dusun Glaran I have changed because of the growing tourism activities which concentrated in certain area. As a result, the village patterns has changed and developed closer to the certain facilities. In the contrary, the spatial space in Dusun Bulu tend to be static because the lack of tourism activities. For âgotong royongâ aspect, it was found that in both villages, it has well established. However, if modernity and individualistic aspects began to affect Dusun Glaran I, the keguyubanâ aspect will begin to disappear